Genetic characterization of the Cuban Creole goat through microsatellite markers - Chac?n, E.; Mart?nez, A.; La O, M.; Vel?zquez, F. J.; P?rez, E.; Delgado, J. Vicente (Cuban Journal of Agricultural Science, 2010)
Samples of hair from 40 goats were collected to characterize genetically the Cuban Creole goat as part of the research project for the preservation and improvement of this breed. Out of them, 33 % came from the only genetic nucleus of this breed in Cuba, located in the Genetic Enterprise ?Manuel Fajardo? in Jiguan?, Granma. The rest of the goats were from several farms, cooperatives of agricultural production, and other herds from the provinces of Granma, Santiago de Cuba, and Holgu?n. A set of 26 microsatellites was used, as recommended by the FAO and the International Society of Animal Genetics (ISAG) for studies of genetic diversity in the goat species. The amplification of them was performed through the polymerase chain reaction (PCR) and the amplified fragments were separated by electrophoresis in polyacrylamide gels. The allelic frequencies, the expected (He) and the observed (Ho) heterozygosities, and the polymorphic information content (PIC) were calculated, as well as the Hardy-Weinberg equilibrium (HWE) per marker. The mean value of the alleles per locus was of 6.38. the totality of the loci under study were polymorphic in this breed, and 77 % of them showed high polymorphic information content (PIC). This, along with the presence of more than 58 % of heterozygotic individuals, evidences that the Cuban Creole goat is a breed with self-identity having high genetic diversity. Key words: Creole goats, polymorphism, microsatellites.